Pengembangan Bahan Ajar Tematik Integratif pada Materi Penanggulangan Bencana Alam Siswa Kelas V SDN Tanjungrejo 4 Malang - Alfiatus Safa’ah (Bidayatuna, 2020)
Frequent natural disasters in various areas of Indonesia always need responsive mitigation efforts. In education, this role can be realized by developing teaching materials of natural disaster mitigation. The research was conducted at SDN Tanjungrejo 4 Malang with the research object of 39 fifth grade students. The purpose of this research and development of these materials include to know the process and to know the effectiveness of development of integrative thematic teaching materials in the content of natural disaster mitigation for the fifth grade students. This research is categorized in the Research and Development that was developed by Walter Dick and Lou Carey’s develepomental models. Feasibility of teaching materials can be seen from the validation results of the content’s expert of 94.6%, result validation of the design’s expert is 95.6%, the teacher of fifth grade students is 89.3%, and the students of fifth grade is 86.7% which as a whole can be said to be a valid teaching materials and feasible to use. The effectiveness of this teaching material can be seen from the increasing of the average of student’s learning outcomes. Before the teaching materials were implemented, the average of student’s learning was 58.27 and after using learning materials, the average score was increased to 80.02.